(untitled) (Politeja, 2026)
TOWARDS DIALOGICAL PLURALISM IN INTERNATIONAL RELATIONS – ON THE ROLE, SUBSTANCE AND CONSEQUENCES OF METATHEORETICAL FOUNDATIONS IN RESEARCH PRACTICE The aims of the article are the following: (1) to point out the rung occupied by metatheory on the ladder of abstraction of the actual work of International Relations scholars; (2) to present a typology of possible metatheoretical approaches to the study of international reality; (3) to provide examples of classic IR works that are based on specific metatheoretical approaches; (4) to help particular scholars to identify their own metatheoretical bases using the aforementioned typology and examples; and (5) to propose an approach allowing ideas to flow between approaches based on different metatheories while maintaining the integrating role of the discipline.